2018
DOI: 10.1039/c8cc00386f
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced emission of [3]cumulenes functionalized with heptagon-containing polyphenylenes

Abstract: Turning on the fluorescence of [3]cumulenes: we report the luminescence at room temperature upon aggregation of [3]cumulenes functionalized with propeller-like heptagon-containing polyphenylenes. These endgroups turn on the emission of a [3]cumulene by steric protection and restriction of their intramolecular rotations in the aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“… [74] In one notable example, the cyclization reaction of diyne 76 and alkyne 77 resulted in heptagon‐embedded polyphenylene 78 , which can undergo oxidative cyclization under Scholl reaction conditions to afford fully cyclized heptagon‐containing HBC 79 . Through the installation of different substituents, various derivatives of 78 and 79 have been obtained, many of which featured promising optoelectronic properties including low band gaps and long fluorescence lifetimes [75–81] …”
Section: Extension Of Cycloheptanonesmentioning
confidence: 99%
See 1 more Smart Citation
“… [74] In one notable example, the cyclization reaction of diyne 76 and alkyne 77 resulted in heptagon‐embedded polyphenylene 78 , which can undergo oxidative cyclization under Scholl reaction conditions to afford fully cyclized heptagon‐containing HBC 79 . Through the installation of different substituents, various derivatives of 78 and 79 have been obtained, many of which featured promising optoelectronic properties including low band gaps and long fluorescence lifetimes [75–81] …”
Section: Extension Of Cycloheptanonesmentioning
confidence: 99%
“…Very recently,t he same group successfully synthesized heptabenzo[7]circulene (75), an egatively curved nanographene containing seven adjoined [4]helicene units (Scheme 20). [69] Thes ynthesis involved ring expansion of cyclic ketone 70 followed by triflation to afford 71,which was subjected to Diels-Alder cycloaddition with isobenzofuran 72 to provide cycloadduct 73.T his underwent oxygen bridge cleavage and rearomatization to give 74,which was subjected to the final DDQ-mediated Scholl reaction, yielding the desired product 75.X -ray diffraction analysis on racemic crystals revealed that compound 75 has at wisted saddle topology with approximate C 2 symmetry.T he [7]circulene moiety seen in 75 with asaddle depth of 1.73 is more curved than [7]circulene itself (saddle depth 1.10 )b ecause the [4]helical substructure in 75 induces agreater degree of steric clash.…”
Section: Extension Of Cycloheptanonesmentioning
confidence: 99%
“…By following this strategy, we have synthesized various structures containing seven-membered rings, such as nanoribbons 12c or [3]cumulenes derivatives. 20…”
Section: Syn Lettmentioning
confidence: 99%
“…Extended -conjugated molecules have been widely investigated for their unique physical properties that can be modified by proper molecular design. In particular, much attention has been focused on sterically congested and/or curved polycyclic aromatic hydrocarbons (PAHs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14] as well as cyclic -conjugated molecules like cycloparaphenylenes [15][16][17][18][19][20][21] and carbon nanobelts. [22][23][24] These highly strained molecules are potential candidates with special characteristic features that are not found in normal compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Within such compounds, curved structures for PAHs are efficiently induced by incorporating mediumsized rings, such as seven-membered rings, which impart molecular strain and distortion. 3,4,7,8,10,11,13 For example, we recently reported that highly strained hydrocarbons could be generated by connecting two dibenzocycloheptatriene units with a C-C bond, in which a sevenmembered ring is a key structure to induce severe strain to give a hyper covalent bond with a C-C single bond length beyond 1.8 Å. 25 Such an elongated bond can be cleaved upon two-electron oxidation to give the corresponding stable dication [dynamic redox (dyrex) behavior] to exhibit electrochromic behavior.…”
Section: ■ Introductionmentioning
confidence: 99%